Rhino-orbital mucormycosis due to Apophysomyces ossiformis in a patient with diabetes mellitus: a case report - Erick Martínez-Herrera; María Guadalupe Frías-De-León; Angélica Julián-Castrejón; Luis Cruz-Benítez; Juan Xicohtencatl-Cortes; Rigoberto Hernández-Castro (BMC Infectious Diseases, 2020)
Abstract Background The most common aetiological agents of mucormycosis are Rhizopus, Mucor, Apophysomyces and Lichtheimia. Apophysomyces is comparatively rare, as it has been reported in less than 3% of mucormycosis cases. The genus Apophysomyces includes six species, and only A. elegans, A. mexicanus, A. variabilis and A. ossiformis have been reported to cause infections in both immunocompetent and immunocompromised patients. Case presentation We present a case of a 46-year-old male patient with bilateral blepharoedema, corneal opacity in the left eye and poorly controlled diabetes mellitus. The patient was subjected to total maxillectomy, exenteration of the left orbit and treatment with liposomal amphotericin B. Direct mycological analysis with KOH 10% revealed hyaline, coenocytic, long and wide hyphae. Apophysomyces ossiformis was identified from maxillary biopsy using 18S-ITS1–5.8S-ITS2-28S rRNA gene amplification and sequencing. The patient requested to be transferred to another hospital to continue treatment, where he died on the ninth day after admittance. Conclusion To the best of our knowledge, this is the first case of rhino-orbital mucormycosis due to A. ossiformis with a fatal outcome. This case reveals the need to identify the fungus causing mucormycosis with molecular methods to identify adequate treatment therapies for patients with this infection.